2012
DOI: 10.1007/s00440-012-0435-2
|View full text |Cite
|
Sign up to set email alerts
|

Invariance principle for the random conductance model

Abstract: We study a continuous time random walk X in an environment of dynamic random conductances in Z d . We assume that the conductances are stationary ergodic, uniformly bounded and bounded away from zero and polynomially mixing in space and time. We prove a quenched invariance principle for X, and obtain Green's functions bounds and a local limit theorem. We also discuss a connection to stochastic interface models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
161
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(165 citation statements)
references
References 39 publications
4
161
0
Order By: Relevance
“…It states that, P [⋅ 0 ∈ C ∞ ]-a.s., the process εX ε −2 t t≥0 converges in law, as ε → 0, to a non-degenerate Brownian motion with covariance matrix σI d . This result was extended to the setting considered here (and to even greater generality) by Biskup and Prescott [13] and Mathieu [23] (see also Andres, Barlow, Deuschel and Hambly [1]). We refer to the survey of Biskup [12] and the references therein for more on the many recent works on this problem.…”
Section: 1)supporting
confidence: 55%
See 1 more Smart Citation
“…It states that, P [⋅ 0 ∈ C ∞ ]-a.s., the process εX ε −2 t t≥0 converges in law, as ε → 0, to a non-degenerate Brownian motion with covariance matrix σI d . This result was extended to the setting considered here (and to even greater generality) by Biskup and Prescott [13] and Mathieu [23] (see also Andres, Barlow, Deuschel and Hambly [1]). We refer to the survey of Biskup [12] and the references therein for more on the many recent works on this problem.…”
Section: 1)supporting
confidence: 55%
“…Let ◻ be the largest triadic cube satisfying 1 9 ◻ ⊆ Q. It follows from simple geometric considerations that Q ⊆ ◻.…”
Section: Lemma 36 (Reverse Hölder Inequality) Fix An Exponentmentioning
confidence: 99%
“…(In d = 1, the decay can be arbitrarily slow.) Further progress has been made by Boukhadra [14,15] who showed that the transition from regular decay n −d/2 to anomalous decay n −2+o (1) in d ≥ 5 actually occurs in the class of power-law tails -with the exponent γ = d/2 in P(0 < ω b < s) ∼ s γ being presumably the critical for the anomaly to appear. In d ≥ 5 this meshes nicely with the annealed estimates obtained by Fontes and Mathieu [23].…”
Section: Recentmentioning
confidence: 99%
“…The principal items of interest are various asymptotics of the law of X under P x ω in the situation when ω is a sample from a probability distribution P. Much of the early effort by probabilists concerned the validity of the (functional) Central Limit Theorem. In a sequence of papers (Kipnis and Varadhan [27], De Masi, Ferarri, Goldstein and Wick [19,20], Sidoravicius and Sznitman [34], Berger and Biskup [9], Mathieu and Piatnitski [31], Mathieu [30], Biskup and Prescott [13], Barlow and Deuschel [5], Andres, Barlow, Deuschel and Hambly [1]), it has gradually been established that, as n → ∞, the law of t → X ⌊nt⌋ / √ n under P 0 ω scales to a non-degenerate Brownian motion for almost every environment ω, provided that certain conditions are met by the law of ω. where E denotes the expectation in P and p c (d) is the critical threshold for bond percolation on Z d . In d = 1 the second condition needs to be replaced by E(ω −1 b ) < ∞; independence is not required (e.g., Biskup and Prescott [13]).…”
Section: Recentmentioning
confidence: 99%
“…conductances, that is when P is the product measure which includes e.g. percolation models, it is shown in [1] (building on previous works [9,10,27,28,34]) that a QFCLT holds provided that P[ω(e) > 0] > p c with p c = p c (d) being the bond percolation threshold. In particular no moment conditions such as (3) are needed.…”
mentioning
confidence: 97%